The predicate fabric of abstraction: the hard test of logical inversion - Papageorgiou, Konstantinos G.; Lekkas, Demetrios E. (Epistēmēs Metron Logos, 2019)
The paper starts with an ultra-compact deposition on the two ubiquitous complementary dual pairwise organized methodological procedures of episteme, i.e. the analytic method (analysis – synthesis) & the abstract process (abstraction – structure). Next, the authors examine some ground rules and concepts pervading causality and inference and their junctions, attempting to discriminate between information flow in empiricism and theoretical causality of proof; only then is a connection between them attempted and investigated. In the authors’ effort to establish a consistent theoretical outlook, if not approach, the technique of logical inversions is also used as a partial yet powerful guide elucidating how successful their attempts were. Apart from clarifying some opaque concepts in logic, in set theory and in the staple empiricism of science, this paper also sets the stage for questioning whether some grave flaws could be located in traditional, save ill-founded, notions in hardcore science, on occasion of the par excellence typical example of fundamental and never challenged approaches in physics. The fact that something has been accepted as holding does not at all mean that cracks may not be located in its epistemological makeup at some posterior time. And it is the text’s task here to ask some painful questions and try to set some realistic boundaries to things by aptly utilizing available irresistible standard «tricks» from logic and from the classical scientific method and from reverting to fruitful techniques and to telling examples, pushing hard for convincing answers.